APLIKASI PENILAIAN KINERJA PERAWAT UNGGULAN MENGGUNAKAN PENDEKATAN SAW - Fricles A Sianturi (Jurnal Ilmu Komputer Ruru, 2024)
Evaluating nurse performance is a critical aspect of human resource management in the healthcare sector. This study aims to develop a decision support system that assists management in determining the best-performing nurses using the Simple Additive Weighting (SAW) method. SAW is chosen for its simplicity and capability to handle various evaluation criteria. In this research, nurse performance data were collected from multiple sources, including supervisory reports, patient feedback, and peer assessments. Each evaluation criterion was assigned a weight according to its importance, and the nurse performance scores were calculated using the SAW formula. The process involves normalizing the criteria scores and then aggregating them to generate a composite performance score for each nurse, The main challenges addressed in this study include the subjectivity and inconsistency often associated with manual performance evaluations. By employing the SAW method, the study seeks to minimize biases and ensure a fair assessment of all nurses based on predefined and weighted criteria. This method was chosen because it can perform a ranking process based on criteria and weights and is able to determine the best alternative. System design with Context Diagram, HIPO, DAD and ERD. Application results are nurse reports, overall selection and selection of the best nurses. The results of the functionality test are proven to be successful and the Validity Test has been proven to be 100% valid.